Identification of the clusters of employee brand using FIMIX-PLS and FCM. (2017) - Thamaraiselvan, N.; Sridevi, P.; Arasu, B. Senthil; Srinivasan, Thushara
Ensuring sustenance of service brand using functional difference is arduous in this competitive era. Such brand difference is significantly based on service employees' interaction with customers. A favourable employee brand presented by employees to customers affords service organisations with competitive advantage. This study attempts to identify the optimum number and types of clusters in employee brand of Air India using two modern data mining techniques, viz., finite mixture partial least squares (FIMIX-PLS) and fuzzy c-means (FCM) clustering for decision making. Employees of Air India, Chennai Division were surveyed and four optimum numbers of clusters of employee brand were identified by both FIMIX-PLS and FCM. It was identified that the employees' knowledge of the desired brand (KDB) their satisfaction in terms of psychological contract (PC) varied across clusters. Quality training, developmental programs, internal communication and feedback systems must be focused and enhanced to increase the employees' KDB and PC.